Enhanced potency of immune checkpoint inhibitors against poorly immunological solid tumors by immune stimulatory oncolytic adenoviruses-mediated remodeling of the tumor microenvironment - Hyo Min Ahn; Bo-Kyeong Jung; JinWoo Hong; Dayoung Hong; A-Rum Yoon; Chae-Ok Yun (Molecular Medicine)
Abstract Immune checkpoint inhibitor (ICI) have shown promising results against a variety of solid tumors across clinical trials. However, ICI monotherapy is often ineffective in patients with non-immunogenic tumors that exhibit high level of immunosuppression and low level of tumor infiltrating lymphocytes. To address these limitations, we have investigated a combination of ICIs [anti-PD-1 antibody (αPD-1), anti-PD-L1 antibody (αPD-L1), or anti-CTLA-4 antibody (αCTLA-4)] with several different immune stimulatory oncolytic adenoviruses (Ads) expressing different combinations of antitumor cytokines or immune modulatory factors [e.g., (1) interleukin (IL)-12 and granulocyte-macrophage colony-stimulating factor (GM-CSF; RdB/IL12/GMCSF), (2) IL-12 and short hairpin ribonucleic acid (shRNA) targeting vascular endothelial growth factor (RdB/IL12/shVEGF), (3) IL-12 and decorin (RdB/IL12/DCN), (4) GM-CSF, and thymidine kinase (RdB/IL12/GMCSF-TK), or (5) IL-12, GM-CSF, and relaxin (RdB/IL12/GMCSF-RLX)] to overcome tumor-induced immunosuppression. Through comparative evaluation of combination therapy regimens, our findings have identified αPD-1 as the optimal ICI candidate to synergize with different oncolytic Ads to induce potent antitumor immune response against poorly immunological solid tumors.